Pelestarian dan Pengembangan Seni Ajeng Sinar Pusaka pada Penyambutan Pengantin Khas Karawang - Wikandia, Rosikin (PANGGUNG, 2016)
ABSTRACTÃÂ Ajeng art preservation HamletÃÂ  origin ÃÂ Bambu ÃÂ Duri, Karangpawitan. ÃÂ Karawang,ÃÂ  many obstacles. ÃÂ Passive ÃÂ role of the local artist community, ÃÂ the lack of regeneration ÃÂ culture ÃÂ of origin, not pro-activeÃÂ  good relations ÃÂ between relevant ÃÂ agencies as well as the entry ÃÂ of modern art, the art of Ajeng ÃÂ undeveloped and eroded extinction. ÃÂ Ajeng art is a kind of art that has its peculiari- ties such as art pangajeng-ngajeng ÃÂ (Pangwilujeng) ÃÂ accompanied by Soja dances that were held at the welcoming ÃÂ ceremony ÃÂ the bride or the guest ÃÂ of honor. ÃÂ Through ÃÂ research ÃÂ with qualitative descriptive approach to the socio-cultural ÃÂ aspects in a systematic, empirical, and cultural ÃÂ theory is expected to ÃÂ be the ÃÂ presentation ÃÂ of Ajeng ÃÂ art Maya art aesthetic ÃÂ tradition ÃÂ and loved young people in the conservation and development ÃÂ of the ÃÂ art of Ajeng.ÃÂ Keywords: Ajeng, ÃÂ Dance SojaÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Pelestarian seni Ajeng asal Dusun Bambu Duri, Karang Pawitan. Kabupaten Karawang, banyak mengalami hambatan. Pasifnya peran komunitas seniman setempat, kurang adanya regenerasi budaya asal, tidak pro aktifnya hubungan baik antara dinas terkait serta masuknya kesenian modern, maka seni Ajeng tidak berkembang dan tergerus kepunahan. Seni Ajeng merupakan jenis seni yang memiliki kekhasan seperti seni pangajeng-ngajeng (Pangwilujeng) dengan diiringi tarian Soja yang biasanya dilaksanakan pada acara upacara pengantin atau penyambutan tamu kehormatan. Melalui penelitian dengan pendekatan deskriftif kualitatif pada aspek sosial budaya secara sistematis, empiris, dan teori budaya diharapkan seni Ajeng menjadi penyajian seni Ajeng yang estetik tradisi dan dicintai generasi muda dalam rangka pelestarian dan pengembangan seni Ajeng.ÃÂ Kata kunci: Ajeng, Tari Soja